Critical Regionalism in the Post-Colonial architecture of the Indian subcontinent - Misra, Sumantra; Chakraborty, Manjari; Mandal, N. R. (Journal of Architecture and Urbanism, 2018)
Critical Regionalism as expounded by Kenneth Frampton has found its use in many parts of the world as a reaction to the international architecture practised in the Western world. India, which was deprived of exposure to the advanced developments in architecture in the US and Europe was at one stroke brought into world contact after gaining independence. This paper traces the exposure of the Indian architects to Western training and philosophy and how they developed their works to suit the regional context. Important aspects of the paper are mentioned below: ‒ International exposure of the Indian architects after independence. ‒ Their designs and their approaches to the creation of an Indian flavour on their return to homeland. ‒ Examined the works of a few prominent architects and inferred on their special regional contributions.